Prevalence of cyberchondria among university students: an emerging challenge of the 21st century - Sabeen Sabir; Naqvi, Irum (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate the prevalence of cyberchondria among university students, and to explore their self-diagnosis behaviour. Method: The cross-sectional study was conducted in different cities of Pakistan from September 2021 to July 2022. Participants were approached through purposive sampling at different institutions of higher education and were asked about access to internet. Data was collected using a demographic proforma and through the self-reporting Cyberchondria Severity Scale-Short Version. Data was analysed using SPSS 26. Results: Of the 500 subjects, 248(49.6%) were male and 252(50.4%) were female. The overall mean age of the sample was 24.14±3.68 years (range: 18-45 years). Of the total, 286(57.2%) subjects were diagnosed with some medical condition, 214(42.8%) self-diagnosed themselves, 302(60.4%) rated their health status as fair, 123(24.6%) rated their health status as good, and 320(64%) said they did not check the accuracy of health-related information. The prevalence of cyberchondria was moderate 252(50.4%) to high 119(23.80%) which indicates the severe severity level of cyberchondria among students. The prevalence of cyberchondria was moderate in women 151(60%) compared to men 101(40.7%). Mean scores of women on cyberchondria severity scale were higher than men (p<0.01). Cyberchondria was more prevalent among individuals with diagnosed medical condition (p<0.01) and those who self-diagnose their symptoms via the internet (p<0.001). Conclusions: Cyberchondria must be seen as a serious public health concern in Pakistan. Since it is associated with distress and worry, measures need to be adopted to evaluate, prevent, and treat it at the population level. Key Words: Cyberchondria, Health anxiety, Online health information searches, Self-diagnosis, Diagnosed medical condition.